IMPLEMENTASI PRINSIP-PRINSIP TOTAL QUALITY MANAGEMENT DALAM PENGELOLAAN TENAGA KEPENDIDIKAN DI MTS DARUL IHSAN SAMARINDA - Iqbal Alfiandy; Muthia Umi Setyoningrum; Bahrani; Akhmad Ramli (STKIP Subang, 2025)
This study aims to describe the implementation of Total Quality Management (TQM) principles in the management of educational staff at MTs Darul Ihsan Samarinda. The study focuses on five key TQM principles: customer focus, total involvement, continuous improvement, visionary leadership commitment, and data-based decision-making. This research used a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. The study subjects consisted of the principal, teachers, and administrative staff. The results indicate that TQM implementation at MTs Darul Ihsan has been quite effective, particularly in terms of visionary leadership and staff involvement. The principal plays an active role in building a culture of quality through open communication, staff empowerment, and regular performance evaluations. The principle of continuous improvement is implemented through periodic training and supervision, while the customer focus is realized through student and parent satisfaction surveys. However, challenges remain in the utilization of data and the lack of an integrated quality information system. Overall, the implementation of TQM principles has positively contributed to improving professionalism, discipline, and collaboration among educational staff at MTs Darul Ihsan Samarinda. This study recommends strengthening the data-driven management system, providing ongoing training for educational staff, and improving information technology support to ensure optimal and sustainable TQM implementation.